2009
DOI: 10.1111/j.1365-2516.2009.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ischaemic heart disease in haemophilia patients: an institutional guideline

Abstract: Since the introduction of clotting factor concentrates, life expectancy of haemophilia patients is increasing and now approaches that of the general male population. Increasingly, haemophilia patients are confronted with age-related co-morbidity, including ischaemic cardiovascular disease. Treatment of stable angina pectoris and the acute coronary syndrome with antithrombotic therapy and percutaneous coronary intervention in haemophilia patients is feasible, but requires a tight co-operation between all specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
153
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(154 citation statements)
references
References 23 publications
0
153
0
1
Order By: Relevance
“…The recommended serum level of FVIII is 0.8 U/I pre-catheterization until 48 hours post-catheterization. To achieve this level, the initial bolus of FVIII should be 40 U/kg infused over 30 minutes with a factor recovery assay done 15 minutes later and once peak level is achieved, maintenance is done by slow infusion at 20 U/kg every 12 hours for 48 hours (15). Bleeding is the most common complication especially if attempting femoral access compared to radial access.…”
Section: Patients With Inherited or Acquired High Risks Of Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended serum level of FVIII is 0.8 U/I pre-catheterization until 48 hours post-catheterization. To achieve this level, the initial bolus of FVIII should be 40 U/kg infused over 30 minutes with a factor recovery assay done 15 minutes later and once peak level is achieved, maintenance is done by slow infusion at 20 U/kg every 12 hours for 48 hours (15). Bleeding is the most common complication especially if attempting femoral access compared to radial access.…”
Section: Patients With Inherited or Acquired High Risks Of Bleedingmentioning
confidence: 99%
“…Similar to hemophilia A, these patients have increased risk for hemorrhage and present with bleeding to joints or muscles due to mild trauma or occurring spontaneously. The recommendations for these patients are to transfuse factor IX at 80U/kg precatheterization to have a peak level of 0.8 U/I and once peak level is achieved, maintenance is with slow infusion at 20 U/kg every 12 hours for 48 hours post-catheterization (15).…”
Section: Patients With Inherited or Acquired High Risks Of Bleedingmentioning
confidence: 99%
“…22 Schutgens et al and Mannucci et al underline the necessity to correct clotting factor deficiency in patients with hemophilia before performing a PCI or arterial angiography. 23,24 They recommend a target maximum level of 0.8 UL before PCI, and up to 48 hours after PCI, because a higher level can lead to hypercoagulability and the formation of an occlusive thrombus. Lim et al reported a study which included eight hemophiliacs.…”
Section: The Necessity Of Screening and Risk Of Invasive Investigatiomentioning
confidence: 99%
“…33,44,45 The long-term use of low-dose aspirin in patients with mild or moderate hemophilia has been proposed, but extended use in patients with severe hemophilia may be difficult, even with factor prophylaxis and close monitoring for bleeding. 44 The use of warfarin has generally not been recommended.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Factor replacement to maintain a trough plasma factor level of at least 30 U/dL for the duration of the antiplatelet therapy has been recommended. 33,44 Close laboratory monitoring of factor levels periprocedurally, perioperatively, and during the use of anticoagulants and/or antiplatelet agents is required.…”
Section: Cardiovascular Diseasementioning
confidence: 99%